FREEDOM OF EXPRESSION IN THE DIGITAL AGE: CONSTITUTIONAL LIMITS ON HUMAN RIGHTS RESTRICTIONS UNDER THE 1945 CONSTITUTION OF THE REPUBLIC OF INDONESIA AND JUDICIAL DYNAMICS IN INDONESIA - Sulistyowati Sulistyowati; Dewi Nadya Maharani; Gusti Bintang Maharaja; Rachel Dwita Maharani (International Journal of Multidisciplinary Research and Literature, 2025)
The digital age has fundamentally transformed the way people express their opinions and views. Advances in information and communication technology—particularly the massive penetration of social media in Indonesia—have opened up a space for public participation that is broader, faster, and free from geographical boundaries. Citizens can now easily criticize government policies, report alleged abuses of power, and voice their political aspirations directly through various digital platforms. On the other hand, freedom of expression in the digital sphere often clashes with the interests of public order, national security, social stability, and the protection of the reputation of individuals and institutions. This article aims to conduct an in-depth analysis of the constitutional limits on restrictions of human rights regarding freedom of expression under the 1945 Constitution of the Republic of Indonesia, as well as the judicial dynamics occurring in Indonesia. Using a normative-dogmatic approach supported by an analysis of court rulings, this article finds that while Article 28E(3) and Article 28F of the 1945 Constitution of the Republic of Indonesia provide strong guarantees for freedom of expression, Article 28J(2) provides a valid constitutional basis for restricting that right. Restrictions are only permissible if established by law, aimed at respecting the human rights of others, and meeting fair demands based on moral considerations, religious values, security, and public order in a democratic society. Constitutional Court Decisions No. 105/PUU-XXII/2024 and No. 78/PUU-XXI/2023 have significantly reformed cyber law in Indonesia, including the abolition of the offense of spreading false news that causes public unrest and the restriction of the legal subjects of defamation offenses to only natural persons. This article recommends strengthening restorative justice mechanisms, establishing objective parameters for non-pecuniary damages in civil law, and issuing technical guidelines for law enforcement officials